Association Between Physical Activity, Menstrual Cycle Characteristics and Body Weight in Adolescent Girls in Western Nepal - Bhandari, Keshav Raj; Sapkota, Bibechana; Manandhar, Sujil; Karki, Supendra; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Adolescent girls frequently experience menstrual irregularities that are affected by multiple factors, including body mass index (BMI), exercise habits, nutrition, and sleep routines. This study sought to investigate the relationships among BMI, menstrual cycle disruptions, and lifestyle elements such as exercise, eating habits, and sleep patterns in a group of teenage girls between 13 and 16 years of age. Method: We conducted a cross-sectional investigation of 301 teenagers. The study gathered information on body mass index, menstrual health, exercise habits, eating patterns, and sleep duration. Statistical analyses, including chi-square tests and logistic regression models, were used to examine the relationships between these variables and menstrual irregularities. Result: Participants had a mean age of 14.65 ± 0.86 years. Significant correlations were identified between BMI and factors such as ethnicity, tea intake, and exercise level (p ≤ 0.05). Although no direct link was established between BMI and menstrual irregularity (p = 0.454), certain lifestyle choices were strongly associated with irregular menstruation. These included insufficient physical activity (OR = 2.94, p = 0.042), regular dining out (more than three times weekly; OR = 9.08, p = 0.045), and inadequate rest (p = 0.035). Additionally, dysmenorrhea was significantly associated with menstrual irregularity (p = 0.022), suggesting a possible shared hormonal mechanism underlying both the conditions. Conclusion: Although body mass index (BMI) did not show a direct correlation with menstrual irregularities, various lifestyle elements such as exercise habits, nutritional intake, and hours of sleep were found to be key factors influencing menstrual health. This underscores the crucial role of maintaining a wholesome lifestyle, encompassing regular physical activity, a well-balanced diet, and adequate rest in promoting normal menstrual cycles among teenage girls. Additional long-term research is required to investigate cause-and-effect relationships between these lifestyle factors and disruptions in menstrual patterns.